2016
DOI: 10.1371/journal.pone.0167663
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Lactic Acid) Nanoparticles Targeting α5β1 Integrin as Vaccine Delivery Vehicle, a Prospective Study

Abstract: Biodegradable polymeric nanoparticles are vehicles of choice for drug delivery and have the ability to encapsulate and present at their surface different molecules of interest. Among these bio-nanocarriers, poly(lactic acid) (PLA) nanoparticles have been used as adjuvant and vehicle for enhanced vaccine efficacy. In order to develop an approach to efficient vaccine delivery, we developed nanoparticles to target α5β1 positive cells. We first overproduced, in bacteria, human fibronectin FNIII9/10 recombinant pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Design and molecular dynamics studies of HBV-specific NP formulations PLA NP were prepared according to an adjuvant-free nanoprecipitation method (Lamalle-Bernard et al, 2006) and Pam3CSK4 was simultaneously entrapped in PLA NP as previously described (Lamrayah et al, 2019). Secondly, dPreS1 peptide (2-48 AA construct from a consensus sequence with a N-terminal myristoylation) was added at the surface of the NP by passive adsorption (Dalzon et al, 2016;Pavot et al, 2016). The functionalization of PLA NP by Pam3CSK4 and dPreS1 did not significantly change the colloidal size (150 nm), the surface charge (-65 mV) and the dispersity (0.1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Design and molecular dynamics studies of HBV-specific NP formulations PLA NP were prepared according to an adjuvant-free nanoprecipitation method (Lamalle-Bernard et al, 2006) and Pam3CSK4 was simultaneously entrapped in PLA NP as previously described (Lamrayah et al, 2019). Secondly, dPreS1 peptide (2-48 AA construct from a consensus sequence with a N-terminal myristoylation) was added at the surface of the NP by passive adsorption (Dalzon et al, 2016;Pavot et al, 2016). The functionalization of PLA NP by Pam3CSK4 and dPreS1 did not significantly change the colloidal size (150 nm), the surface charge (-65 mV) and the dispersity (0.1) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradable polymeric NP are one of the most extensively studied in the field for their low immunogenicity and biocompatibility and our previous results showed the polylactic acid (PLA) as a great polymer candidate for such scaffolds (Coolen et al, 2019;Pavot et al, 2016;Rességuier et al, 2017). They offer a versatile platform for vectorization (Pavot et al, 2013) and/or adsorption (Dalzon et al, 2016) of various molecules (Ag, immunomodulators) and are promising candidates for vaccine development (Gutjahr et al, 2016;Peres et al, 2017). Yan et al elegantly identified the myristoylated oligopeptide (amino acids sequence 2-48) named PreS1 from the large surface protein, as the molecule enabling HBV to enter into the hepatocyte (Yan et al, 2012) through a high-affinity binding with the sodium taurocholate cotransporting polypeptide (NTCP) receptor (Meier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To further promote liver targeting and avoid spleen accumulation, galactosyl or folate or transferrin could be co-adsorbed on the NP T-B surface to facilitate active liver targeting. Co-adsorption of peptide or proteins has been reported before on such PLA particles, for example by p24 and RGD proteins on PLA NPs, for vaccine development purposes [ 72 ]. It is also worth noting that no toxicity (as evaluated by body weight monitoring and transaminase analysis) was observed in ob/ob mice injected twice per week with NP and NP T-B for a total of 5 weeks ( Supplementary Figure S5 ), suggesting that repeated administration of the formulations is well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…The colloidal stability and dispersity of the fabricated nanoparticles is very important for the biological applications of nanoparticles [ 30 ]. The Zeta potential in PBS solution of PLA NPs or PLA-coated NPs are − 49 mV [ 31 ] and − 63.95 ± 1.29 mV [ 32 ], respectively, suggesting that both of PLA NPs and PLA-coated NPs for drug delivery system as stable drug carriers. In our dynamic light scattering (DLS) experiment, the PLA coated MSNPs suspensions were stable over the period of 1 h with no observable changes in the size distribution of the particles (Additional file 1 : Figure S3).…”
Section: Discussionmentioning
confidence: 99%